PENGARUH METODE MENGGAMBAR DENGAN JARI DAN PENSIL TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK - Lutfiyati Unsiyah Zulfa; Novita Loka (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Providing stimulus to children must be done optimally, especially in the aspect of children's fine motor development. Many of the children in group B are still lacking in maximizing aspects of children's motor development. While group B, the child's motoric development should have gone to maturity because it is to prepare children for the next level. Researchers want to know how much influence the finger drawing and pencil drawing methods have on the fine motor development aspects of children in group B at RA Al Anwar Mrican, Kediri City. This research uses experimental quantitative research. Data analysis using t-test. Respondents in the study were 15 children in group B. The technique of collecting data was by doing a pre-test first, then giving treatment and then doing a post-test. While the data analysis technique was the t-test. The results showed that there was an effect of the finger drawing and pencil drawing methods on the fine motor development aspects of children in group B in RA Al Anwar Mrican, Kediri City. Based on the results of the pairet t test of children's fine motor skills, the p value is 0.000 <0.05.